Assessment and Forecast of Atmospheric Air Quality at the Regional Level. Example of Central Kazakhstan - BEISENOVA, Raikhan; ZHUMASHEV, Bektemir; TAZITDINOVA, Rumiya; RAKHYMZHAN, Zhanar; TULEGENOVA, Symbat; ZHAZNAYEVA, Zhanat (Journal of Environmental Management and Tourism, 2023)
One of the main issues of environmental protection is the quality of atmospheric air. The reason for this is that all life on Earth, first of all, needs air, which affects all climatic and biological processes in general. Harmful and dangerous impurities can be transferred alongside the movement of air masses. These problems are especially acute in industrialized regions, where the level of anthropogenic impact is increasing. These regions include Central Kazakhstan. When studying the issues of ecological and economic development of such regions, it is necessary to consider all possible consequences of anthropogenic impact that affect or may affect the atmospheric air. The main factor which plays a key role in this is strengthening the forecasting functions of environmental monitoring services, in our case, in relation to atmospheric air, and, when drawing up a plan for the infrastructure of the territories, taking into account the level of anthropogenic impact.